1999
DOI: 10.1074/jbc.274.27.18887
|View full text |Cite
|
Sign up to set email alerts
|

Adenylyl Cyclase, a Coincidence Detector for Nitric Oxide

Abstract: Nitric oxide (NO) donors inhibit hormone-and forskolin-stimulated adenylyl cyclase activity in purified plasma membrane preparations from N18TG2 neuroblastoma cells. Northern blot analyses indicate that the predominant isoform of adenylyl cyclase in N18TG2 cells is the type VI. Our experiments eliminate all the known regulatory proteins for this isoform as possible targets of NO. NO decreases the V max of the enzyme without altering the K m for ATP. Occupancy of the substrate-binding site protects the enzyme f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
68
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 26 publications
6
68
1
Order By: Relevance
“…We observed that inhibition of adenylyl cyclase activity and PKA completely blocked the lipolytic effect of iNOS inhibition, implying that NO suppresses lipolysis by reducing cAMP and PKA activation. Interestingly, previous reports have shown that NO inhibits adenylyl cyclase activity (29,30). Thus, the NO donor sodium nitroprusside was found to decrease forskolin-induced activation of type VI adenylyl cyclase.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that inhibition of adenylyl cyclase activity and PKA completely blocked the lipolytic effect of iNOS inhibition, implying that NO suppresses lipolysis by reducing cAMP and PKA activation. Interestingly, previous reports have shown that NO inhibits adenylyl cyclase activity (29,30). Thus, the NO donor sodium nitroprusside was found to decrease forskolin-induced activation of type VI adenylyl cyclase.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is evidence that NO decreases steroidogenesis although in different experimental schemes (Olson et al 1996, Masuda et al 1997, Vega et al 2000. The mechanisms involved may be related to the inhibition produced by the NO of the activity of steroid synthesislimiting enzyme, cytochrome P 450 , of the two isoforms of adenylyl cyclase, the second intracellular messenger (McVey et al 1999), and/or of the inhibition of the steroidogenic acute regulatory protein (StAR) protein (Devoto et al 2001). In our case it should be emphasized that the terminals of the ovarian nervous plexus reach the steroidogenic cells where the inducible NOS or eNOS isoenzymes have been found (Dunnam et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant AC Is Inhibited by Zn 2ϩ -N18TG2 cells appear to express AC6 as their predominant activity (18). To determine whether AC itself is the target of Zn 2ϩ inhibition, we examined recombinant AC6.…”
Section: Kinetic Analyses Of the Effects Of Znmentioning
confidence: 99%